2023
DOI: 10.1088/1748-9326/aceb7b
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition and emission characteristics of CO2 and CH4 in glacial lakes of the Tibetan Plateau

Abstract: Carbon dioxide (CO2) and methane (CH4) emissions from freshwater ecosystems are predicted to increase under climate warming. However, freshwater ecosystems in glacierized regions differ critically from those in non-glacierized regions. The potential emissions of CO2 and CH4 from glacierized environments in the Tibetan Plateau (TP) were only recently recognized. Here, the first direct measurement of CO2 and CH4 emission fluxes and isotopic composition during spring of 2022 in 13 glacial lakes of the TP revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
(82 reference statements)
2
4
0
Order By: Relevance
“…This conclusion is comparable with proglacial river runoff on the Tibetan Plateau (Wang et al, 2014;Yu et al, 2023;Zhang, Ran, et al, 2021;Zhang, Kang, et al, 2021). Recent investigations into the roles of glacier meltwater at glacier terminus in high mountain glaciers as CO2 sources or sinks have shown variable responses to environmental fluctuations (Du et al, 2022;Yan et al, 2023). However, in the maritime glacier regions of the southeastern Tibetan Plateau, it serves as a potential CO2 sink.…”
Section: Co 2 Influx and Consumptionsupporting
confidence: 65%
See 1 more Smart Citation
“…This conclusion is comparable with proglacial river runoff on the Tibetan Plateau (Wang et al, 2014;Yu et al, 2023;Zhang, Ran, et al, 2021;Zhang, Kang, et al, 2021). Recent investigations into the roles of glacier meltwater at glacier terminus in high mountain glaciers as CO2 sources or sinks have shown variable responses to environmental fluctuations (Du et al, 2022;Yan et al, 2023). However, in the maritime glacier regions of the southeastern Tibetan Plateau, it serves as a potential CO2 sink.…”
Section: Co 2 Influx and Consumptionsupporting
confidence: 65%
“…Under natural conditions, the solubility of carbonates is about 12-40 times higher than that of silicates (Meybeck, 1987;Pant et al, 2018). 2023) is primarily during the beginning of the glacier melting period (spring), whereas our sampling period is during the monsoon period (summer) and the post monsoon period (winter); (c) CO 2 flux of the 13 glacial lakes measured by Yan et al (2023) varies widely from 0.5 ± 2.6 to 13.8 ± 10.4 mmol m 2 d 1 , which encompasses our calculated CO 2 flux. Shukla et al ( 2023) estimated CO 2 flux of the Himalayan glacier-fed lakes and found that these lakes were potential CO 2 sources, with a CO 2 efflux of 1,746 ± 139 mg C m 2 d 1 .…”
Section: Co 2 Influx and Consumptionmentioning
confidence: 99%
“…Although Xun et al (2022) stressed salt lakes that generally show higher pCO 2 than freshwater, Li, Shi, et al (2022) surprisingly found that frozen salt lakes have a strong CO 2 uptake potential during the ice-covered period. In addition, while melting of glaciers and permafrost will provide sufficient soil organic matter for CO 2 production (thus a CO 2 source) (Piao et al, 2019), glacial meltwater could accelerate rock weathering, thereby enhancing dissolved CO 2 consumption and sustaining the lake pCO 2 below the atmospheric equilibrium (thus a CO 2 sink) (Yan, Du, et al, 2023). Furthermore, the expanding lake surface due to glacier and permafrost thaw, coupled with the accelerated development of thermokarst lakes, raises the question of whether the increase in water surface enhances C sequestration or exacerbates C emissions (Mu et al, 2023;Yan, Du, et al, 2023).…”
Section: Carbon Dynamics On the Tibetan Plateaumentioning
confidence: 99%
“…In addition, while melting of glaciers and permafrost will provide sufficient soil organic matter for CO 2 production (thus a CO 2 source) (Piao et al., 2019), glacial meltwater could accelerate rock weathering, thereby enhancing dissolved CO 2 consumption and sustaining the lake p CO 2 below the atmospheric equilibrium (thus a CO 2 sink) (Yan, Du, et al., 2023). Furthermore, the expanding lake surface due to glacier and permafrost thaw, coupled with the accelerated development of thermokarst lakes, raises the question of whether the increase in water surface enhances C sequestration or exacerbates C emissions (Mu et al., 2023; Yan, Du, et al., 2023). An accurate assessment of the impacts of temperature increase on C emissions requires the integration of multiple biogeochemical processes of C transport and transformation.…”
Section: Current Research Gaps and Challengesmentioning
confidence: 99%
“…There are fewer studies of CO 2 and CH 4 variations in mountainous lakes than in lowland lakes. Available data suggest that there is no systematic difference in CH 4 emissions between mountainous and lowland lakes, while CO 2 emissions seem to be lower in mountainous lakes that occasionally act as sinks for atmospheric CO 2 , based on data mainly collected in the Alps (Pighini et al 2018), Rocky Mountains (McCrackin andElser 2011;Crawford et al 2015), Sierra Nevada (Cohen and Melack 2020), and the Tibetan Plateau (Yan et al 2018(Yan et al , 2023Wang et al 2022). Available data sets of GHG emissions from lakes and rivers are also spatially skewed toward higher latitudes, mainly in North America and Scandinavia.…”
Section: Introductionmentioning
confidence: 99%